The Library and Commonplace Books of Mary Booth of Dunham Massey (1704–1772). (23rd December 2022) - Potten, Edward
Abstract: This paper offers a detailed case study of Mary Booth as book owner and book user using two primary sources: her surviving library and her commonplace books. Booth's fastidious approach to marking her books, coupled with the fortunate survival of the two houses where those books ultimately came to rest, allows for the reconstruction of her library almost in its entirety. Her commonplace books present an unusually rich record of her reading. Together, these sources offer a rare insight into the life, education, and book use of an early eighteenth-century gentlewoman, a rare comparator against which other women's collections and habits of reading can be assessed.